The Contributions of Arterial Cross-Sectional Area and Time-Averaged Flow Velocity to Arterial Blood Flow - Hill, Ethan C. (J Med Ultrasound, 2018)
BACKGROUND: Ultrasound has been used for noninvasive assessments of endothelial function in both clinical and athletic settings and to identify changes in muscle blood flow in response to exercise, nutritional supplementation, and occlusion. The purposes of the present study were to examine the reliability and relative contributions of arterial cross-sectional area and time-averaged flow velocity to predict muscle blood flow as a result of fatiguing exercise in men and women. METHODS: Eighteen healthy men and 18 healthy women performed 50 consecutive eccentric repetitions of the elbow flexors at 60% of their pretest eccentric peak torque at a velocity of 180° s(−1). Test-retest reliability and stepwise linear regression analyses were performed to determine the ability of arterial cross-sectional area and time-averaged flow velocity to predict brachial artery muscle blood flow for the men, women, and combined sample. RESULTS: There was no systematic test versus retest mean differences (P > 0.05) for any of the ultrasound determined variables. The two-variable regression models significantly improved the ability to predict muscle blood flow and were associated with smaller standard error of the estimates (3.7%–10.1% vs. 16.8%–37.0% of the mean baseline muscle blood flow values) compared to the one-variable models. CONCLUSIONS: The findings of the present study supported the use of ultrasound for reliable assessments of arterial diameter, arterial cross-sectional area, time-averaged flow velocity, and muscle blood flow from the brachial artery in men and women. Furthermore, time-averaged flow velocity was a more powerful predictor of muscle blood flow than arterial cross-sectional area.